A Bio-Inspired Gateway Selection Scheme for Hybrid Mobile Ad Hoc Networks - Xu, Huaqiang; Zhao, Yuefeng; Zhang, Liren; Wang, Jingjing (IEEE access, 2019)
The gateway selection is an essential issue in hybrid mobile ad hoc networks (MANETs). Current independent and random selections without supporting routing negotiation protocol may cause links or gateways overloaded when they are selected by multiple nodes simultaneously. Therefore, the network performance may not be in a proper way. Furthermore, the ad hoc nature of MANETs makes the topology change dynamically, so that the gateway selection becomes even more difficult. This paper presents a mathematical model for gateway capability and a novel approach, called bio-inspired gateway selection, where the gateways are selected according to the network status and associated with a cooperative mechanism for optimization. The novelty includes the use of attractor selection model, the self-adaptability and the autonomy of the biological system. The performance of the proposed approach is evaluated by simulation with different scenarios and compared with the conventional approaches being currently used in hybrid MANETs. The illustrated numerical results present the performance of the proposed approach in terms of packet delivery ratio, average delivery latency, normalized routing overhead, and gateway load balance under different network conditions. Furthermore, the numerical results are also able to demonstrate the significant performance gain compared with the conventional gateway selection approaches.